1997
DOI: 10.1093/genetics/147.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Interactions Between HOP1, RED1 and MEK1 Suggest That MEK1 Regulates Assembly of Axial Element Components During Meiosis in the Yeast Saccharomyces cerevisiae

Abstract: During meiosis, axial elements are generated by the condensation of sister chromatids along a protein core as precursors to the formation of the synaptonemal complex (X). Functional axial elements are essential for wild-type levels of recombination and proper reductional segregation at meiosis I. Genetic and cytological data suggest that three meiosis-specific genes, HOP1, RED1 and MEK1, are involved in axial element formation in the yeast Saccharomyces cerevisiae. HOP1 and RED1 encode structural components of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(33 citation statements)
references
References 46 publications
4
29
0
Order By: Relevance
“…In a scenario similar to the rad50S checkpoint, a macromolecular assembly of the meiotic chromosomal proteins Hop1, Red1 and Mek1 is thought to provide a framework for the activation of the recombination checkpoint [43,48,52,59,60]. The correct localization of these proteins to chromosomes appears to depend in part on the histone methyltransferase Dot1 [61].…”
Section: The Recombination Checkpointmentioning
confidence: 99%
“…In a scenario similar to the rad50S checkpoint, a macromolecular assembly of the meiotic chromosomal proteins Hop1, Red1 and Mek1 is thought to provide a framework for the activation of the recombination checkpoint [43,48,52,59,60]. The correct localization of these proteins to chromosomes appears to depend in part on the histone methyltransferase Dot1 [61].…”
Section: The Recombination Checkpointmentioning
confidence: 99%
“…In budding yeast, the Red1 protein localizes to AEs and is required for the formation of AEs (Smith and Roeder, 1997). Hop1 interacts with, and localizes to the same sites as, Red1, and the localization of Hop1 to AE is dependent on Red1 (Hollingsworth and Ponte, 1997;Smith and Roeder, 1997;de los Santos and Hollingsworth, 1999). Additionally, genetic studies have shown that the stoichiometry of Red1 and Hop1 is critical for AE assembly (Friedman et al, 1994;Hollingsworth and Ponte, 1997).…”
mentioning
confidence: 99%
“…Hop1 interacts with, and localizes to the same sites as, Red1, and the localization of Hop1 to AE is dependent on Red1 (Hollingsworth and Ponte, 1997;Smith and Roeder, 1997;de los Santos and Hollingsworth, 1999). Additionally, genetic studies have shown that the stoichiometry of Red1 and Hop1 is critical for AE assembly (Friedman et al, 1994;Hollingsworth and Ponte, 1997). Mek1 is a meiosis-specifi c serine/threonine kinase involved with the SC assembly, and it interacts with Red1 physically and genetically.…”
mentioning
confidence: 99%
“…In budding yeast, this chromosomal axis is established on cohesin complexes (containing the meiosis-specific kleisin subunit Rec8) (Klein et al 1999 ). In addition to cohesin, it contains the HORMA-domain protein Hop1 and the coiled coil-containing protein Red1 (de los Santos and Hollingsworth 1999 ; Hollingsworth et al 1990 ; Hollingsworth and Ponte 1997 ; Klein et al 1999 ; Smith and Roeder 1997 ; Sym et al 1993 ). An additional axis-component is Mek1, a meiosis-specific protein kinase that functions in the meiotic checkpoint and promotes repair of DSBs using sequences present on homologous chromosomes (Hollingsworth and Ponte 1997 ; Niu et al 2005 ; Wan et al 2004 ).…”
Section: Meiosismentioning
confidence: 99%
“…In addition to cohesin, it contains the HORMA-domain protein Hop1 and the coiled coil-containing protein Red1 (de los Santos and Hollingsworth 1999 ; Hollingsworth et al 1990 ; Hollingsworth and Ponte 1997 ; Klein et al 1999 ; Smith and Roeder 1997 ; Sym et al 1993 ). An additional axis-component is Mek1, a meiosis-specific protein kinase that functions in the meiotic checkpoint and promotes repair of DSBs using sequences present on homologous chromosomes (Hollingsworth and Ponte 1997 ; Niu et al 2005 ; Wan et al 2004 ). This specialized chromosome architecture facilitates DNA break activity, checkpoint function, and interhomolog-based recombinational CO repair in meiotic G2/prophase (Carballo et al 2008 ; Humphryes and Hochwagen 2014 ; Panizza et al 2011 ; Zickler and Kleckner 1999 ).…”
Section: Meiosismentioning
confidence: 99%